The Influence of Adiministrative Sanctions and Motor Vehicle Taxpayer Awareness on Tax Payment Compliance at The Pangkep Regency Samsat Office - Andi Nur Alamsyah Arsyad; Masrullah; Indriana (www.amertainstitute.com, 2025)
The objective of this study is to analyze the effect of administrative sanctions and taxpayer awareness on the compliance of motor vehicle tax payments at the Samsat Office in Pangkep Regency. The research uses a quantitative approach by distributing questionnares to 100 respondets who are motor vehicle taxpayers. An analysis was conducted on the data using multiple linier regressions with the help of Statistical Package for the Social Science (SPSS) software version 30. The results show that both administrative sanctions and tax payer awareness exert a favorable and statistically significant impact on motor vehicle tax payment compliance. These findings suggest that enhancing the effectiveness of sanctions and improving public tax awareness can promote taxpayer compliance, thereby supporting the increase of regional tax revenue.